Mechanism of the hydrophobic effect in the biomolecular recognition of arylsulfonamides by carbonic anhydrase - Snyder, Phillip W. (National Academy of Sciences, 2011)
The hydrophobic effect—a rationalization of the insolubility of nonpolar molecules in water—is centrally important to biomolecular recognition. Despite extensive research devoted to the hydrophobic effect, its molecular mechanisms remain controversial, and there are still no reliably predictive models for its role in protein–ligand binding. Here we describe a particularly well-defined system of protein and ligands—carbonic anhydrase and a series of structurally homologous heterocyclic aromatic sulfonamides—that we use to characterize hydrophobic interactions thermodynamically and structurally. In binding to this structurally rigid protein, a set of ligands (also defined to be structurally rigid) shows the expected gain in binding free energy as hydrophobic surface area is added. Isothermal titration calorimetry demonstrates that enthalpy determines these increases in binding affinity, and that changes in the heat capacity of binding are negative. X-ray crystallography and molecular dynamics simulations are compatible with the proposal that the differences in binding between the homologous ligands stem from changes in the number and organization of water molecules localized in the active site in the bound complexes, rather than (or perhaps in addition to) release of structured water from the apposed hydrophobic surfaces. These results support the hypothesis that structured water molecules—including both the molecules of water displaced by the ligands and those reorganized upon ligand binding—determine the thermodynamics of binding of these ligands at the active site of the protein. Hydrophobic effects in various contexts have different structural and thermodynamic origins, although all may be manifestations of the differences in characteristics of bulk water and water close to hydrophobic surfaces.